2020
DOI: 10.1200/jco.20.00808
|View full text |Cite
|
Sign up to set email alerts
|

Phase Ib Study of Lenvatinib Plus Pembrolizumab in Patients With Unresectable Hepatocellular Carcinoma

Abstract: PURPOSE The immunomodulatory effect of lenvatinib (a multikinase inhibitor) on tumor microenvironments may contribute to antitumor activity when combined with programmed death receptor-1 (PD-1) signaling inhibitors in hepatocellular carcinoma (HCC). We report results from a phase Ib study of lenvatinib plus pembrolizumab (an anti–PD-1 antibody) in unresectable HCC (uHCC). PATIENTS AND METHODS In this open-label multicenter study, patients with uHCC received lenvatinib (bodyweight ≥ 60 kg, 12 mg; < 60 kg, 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
825
13
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 889 publications
(875 citation statements)
references
References 25 publications
34
825
13
3
Order By: Relevance
“…Co-targeting the PD-(L)1 and VEGF signaling axes is the most extensively studied combination approach for advanced HCC (188,189). Results from single-arm studies showed that combinations of VEGF and PD-(L)1 inhibitors were associated with a manageable safety profile and promising antitumor activity, with ORRs of 11% to 50% (190)(191)(192)(193)(194)(195).…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…Co-targeting the PD-(L)1 and VEGF signaling axes is the most extensively studied combination approach for advanced HCC (188,189). Results from single-arm studies showed that combinations of VEGF and PD-(L)1 inhibitors were associated with a manageable safety profile and promising antitumor activity, with ORRs of 11% to 50% (190)(191)(192)(193)(194)(195).…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…Accordingly, immune checkpoint inhibitors will gain an important position in the treatment of HCC. A phase 1b study of lenvatinib plus pembrolizumab showed an ORR of 46%, as assessed by mRECIST and 36%, as assessed by RECIST ver.1.1 [109]. The median PFS, as assessed by mRECIST and RECIST ver.1.1, was 9.3 months (95% CI 5.6-9.7) and 8.6 months (95% CI 7.1-9.7), respectively, while the median OS was 22.0 (20.4-not estimable) months [109].…”
Section: Lenvatinib Plus Pembrolizumab Therapymentioning
confidence: 99%
“…A phase 1b study of lenvatinib plus pembrolizumab showed an ORR of 46%, as assessed by mRECIST and 36%, as assessed by RECIST ver.1.1 [109]. The median PFS, as assessed by mRECIST and RECIST ver.1.1, was 9.3 months (95% CI 5.6-9.7) and 8.6 months (95% CI 7.1-9.7), respectively, while the median OS was 22.0 (20.4-not estimable) months [109]. These results of the phase 1b study of lenvatinib plus pembrolizumab demonstrated promising antitumor effects in advanced HCC.…”
Section: Lenvatinib Plus Pembrolizumab Therapymentioning
confidence: 99%
“…To overcome this heterogeneity, studies have investigated the synergic benefits of combination therapy for advanced HCC (40). Lenvatinib combined with pembrolizumab or bevacizumab with atezolizumab demonstrated unprecedented objective response rates (41,42). These reports suggest that the resistance to immune checkpoint inhibitors can be overcome by the combination of drugs with different mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%